Central inhibition of granulocyte-macrophage colony-stimulating factor is analgesic in experimental neuropathic pain. Issue 3 (March 2018) - Nicol, Louise S.C.; Thornton, Peter; Hatcher, Jon P.; Glover, Colin P.; Webster, Carl I.; Burrell, Matthew; Hammett, Kessia; Jones, Clare A.; Sleeman, Matthew A.; Billinton, Andrew; Chessell, Iain
Abstract : Abstract: With less than 50% of patients responding to the current standard of care and poor efficacy and selectivity of current treatments, neuropathic pain continues to be an area of considerable unmet medical need. Biological therapeutics such as monoclonal antibodies (mAbs) provide better intrinsic selectivity; however, delivery to the central nervous system (CNS) remains a challenge. Granulocyte-macrophage colony-stimulating factor (GM-CSF) is well described in inflammation-induced pain, and early-phase clinical trials evaluating its antagonism have exemplified its importance as a peripheral pain target. Here, we investigate the role of this cytokine in a murine model of traumatic nerve injury and show that deletion of the GM-CSF receptor or treatment with an antagonizing mAb alleviates pain. We also demonstrate enhanced analgesic efficacy using an engineered construct that has greater capacity to penetrate the CNS. Despite observing GM-CSF receptor expression in microglia and astrocytes, the gliosis response in the dorsal horn was not altered in nerve injured knockout mice compared with wild-type littermate controls as evaluated by ionized calcium binding adapter molecule 1 (Iba1) and glial fibrillary acidic protein, respectively. Functional analysis of glial cells revealed that pretreatment with GM-CSF potentiated lipopolysaccharide-induced release of proinflammatory cytokines. In summary, our data indicate that GM-CSF is a proinflammatory cytokine that contributes to nociceptive signalling through driving spinal glial cell secretion of proinflammatory mediators. In addition, we report a successful approach to accessing CNS pain targets, providing promise for central compartment delivery of analgesics. Abstract : Supplemental Digital Content is Available in the Text.GM-CSF is a proinflammatory cytokine that plays a role in central pain pathways through the modulation of spinal glial cells.